The Influence of Islamic Marketing Values on Customer Decisions and Repeat Intention in Islamic Banking - Syahruddin Yasen (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid growth of Islamic banking in Indonesia has not been matched by consistent customer loyalty, raising questions about the effectiveness of Islamic marketing strategies. This study aims to analyze the influence of Islamic marketing values on customers’ repeat intention toward Islamic banks in South Sulawesi, with customer decision-making as a mediating variable. The Islamic marketing values examined include Islamic quality management, Islamic bank promotion, Islamic product characteristics, and individual thought characteristics. A quantitative approach was employed using a survey of 200 respondents. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results indicate that promotion and product characteristics have a significant effect on customer decision-making, while quality management and individual thought characteristics do not. Furthermore, customer decision-making strongly affects repeat intention and mediates the relationship between promotional strategies, product features, and loyalty. Promotion also directly impacts repeat intention, underlining the importance of transparent and Sharia-compliant communication. The results highlight that customer loyalty is not merely shaped by religiosity but by how effectively Islamic principles are operationalized and communicated through products and marketing.